Traditional cultivation of sunnhemp (Crotalaria juncea) in eastern India - CHAUDHARY, BABITA (The Indian Journal of Agricultural Sciences, 2016)
Traditional farming method plays an important role in human civilization. Indigenous knowledge is declining because of new agricultural technology has replaced traditional cultivation. But in the some part of country like Eastern Uttar Pradesh and Northern Madhya Pradesh (Bundelkhand Region), social/tribal communities are keeping preserve the traditional knowledge. A survey was made in the villages of five districts of Eastern Uttar Pradesh (Mahoba, Banda, Rath, Chitrkoot and Hamirpur) and one district of Northern part of Madhya Pradesh (Chhattarpur). The study was conducted on indigenous knowledge of sunnhemp (Crotalaria juncea L.) fibre cultivation in Bundelkhand region in India where the social/tribal communities are still preserving the traditional cultivation of sunnhemp as fiber crop.